The Penguinisation of Ibsen - Rem, Tore (Nordlit, 2015)
This article investigates the current generation of Penguin Ibsen editions, translated by Una Ellis-Fermor and Peter Watts and dating back to the 1950s and ‘60s. It sketches the development of Penguin’s publishing profile, and goes on to consider the role played by Penguin Classics in maintaining Ibsen as a central writer in the Western canon, and, with time, in world literature. By examining paratexts, materiality and translation strategies, the main part of the article considers how these editions construct their particular Ibsens. It looks, among other things, at the organisational principles and the scholarly apparatus. The article concludes by briefly noting some possible ambitions for, as well as challenges facing, a new generation of Penguin Ibsen editions.